Multiply the first equation by -3
Multiply the second equation by 2
you'll get:
-12x - 15y = -45
12x - 8y = 22
add them together, then you get:
-23y = -23
y = 1
then sub y back in:
4x +5(1)=15
4x = 10
x = 5/2
2007-01-10 13:07:57
·
answer #1
·
answered by Cris 2
·
1⤊
0⤋
Here is the general way to handle these problems.
1. You need to multiply the first equation by a number, so that
when you add it to the second, you eliminate either x or y.
2. Then solve for the remaining x or y.
3. Whichever variable you get (x or y), plug it into one of the
equations to get the other variable.
Here is the answer in this case.
1. Multiply the first equation by -6/4. You will get:
-6x - (30/4)y = -90/4
6x - 4y = 11
2. Add the two equations together. You get:
0 - (46/4)y = -(46/4), so y = 1.
3. Using the first equation, we have
4x + 5y = 4x + 5*1 = 15, so x = 5/2
4. So the solution is x = 5/2, y = 1.
2007-01-10 13:12:35
·
answer #2
·
answered by Edward W 4
·
1⤊
0⤋
Simplifying
4x + 5y = 15
Solving
4x + 5y = 15
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-5y' to each side of the equation.
4x + 5y + -5y = 15 + -5y
Combine like terms: 5y + -5y = 0
4x + 0 = 15 + -5y
4x = 15 + -5y
Divide each side by '4'.
x = 3.75 + -1.25y
Simplifying
x = 3.75 + -1.25y
and
Simplifying
6x + -4y = 11
Solving
6x + -4y = 11
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '4y' to each side of the equation.
6x + -4y + 4y = 11 + 4y
Combine like terms: -4y + 4y = 0
6x + 0 = 11 + 4y
6x = 11 + 4y
Divide each side by '6'.
x = 1.833333333 + 0.6666666667y
Simplifying
x = 1.833333333 + 0.6666666667y
2007-01-16 12:54:29
·
answer #3
·
answered by love e 1
·
0⤊
0⤋
Given:
4x+5y=15
6x-4y=11
Step 1:
6(4x+5y=15)
4(6x-4y=11)
Step 2:
24x+30y=80
24x-16y=44
Step 3:
14Y=36
Step 4:
Y=2.57
Step 5:
4x+ 5(2.57)=15
4x=2.15
x=0.54
2007-01-18 12:53:41
·
answer #4
·
answered by Ohad 1
·
0⤊
0⤋
4x+5y=15 4x+5y=15
x=0 y=0
4(0)+5y=15 4x+5(0)=15
0+5y=15 4x+0=15
5y=15 4x=15
5y/5=15/5 4x/4=15/4
y=3 x=3.75
point 1- (0,3) point 2- (3.75,0)
graph these two pints in a graph and it will give you a line.
do the same for 6x-4y=11
2007-01-16 11:53:24
·
answer #5
·
answered by cinthia 1
·
0⤊
0⤋
Multiply the first equation by 4 and the second equation by 5:
16x+20y=60
30x-20y=55
=========
46x=115
x=115/46=
5/2
4(5/2)+5y=15
10+5y=15
5y=5
y=1
The solution set is (5/2,1)
Check:
4(5/2)+5(1)=15
10+5=15
15=15
6(5/2)-4(1)=11
15-4=11
11=11
2007-01-10 13:18:42
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
4x + 5y = 15
x =15 -5y / 4
6x - 4y = 11
6(15 - 5y) -16y = 44
90 -30y -16y = 44
90 - 46y = 44
90 - 44 = 46y
46 = 46y
y = 1
x = 15 - 5*1 /4
x = 15-5 / 4
x = 10/4
x = 5/2
2007-01-16 20:39:42
·
answer #7
·
answered by arunima 2
·
0⤊
0⤋
8x+7y=32 __(a million) -6x+3y=-24 ___(2) [multiply (a million) by potential of three and (2) by potential of four] 24x + 21y = ninety six __(3) -24x + 12y = -ninety six __(4) [upload (3) and (4)] 33y = 0 y = 0 [from (a million)] 8x + 7(0) = 32 8x = 32 x = 32/8 x = 4 so (x,y) = (4,0) ANS. (a)
2016-11-28 03:06:05
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
equation 3: equation 1*3= 12x+15y=45
equation 4: equation 2*2= 12x-8y=22
3-4: 23y=23
so y=1
then 12x+15=45
12x=30
x=2.5
2007-01-10 13:05:30
·
answer #9
·
answered by dark magician girl 1
·
1⤊
0⤋
Hi,
4X+5Y=15 -->Multiply row by 6
6X-4Y=11 --->Multiply row by 4
----------------------------------------------
24X+30Y=90
24X-16Y=44
- + -
-----------------------
0+46Y=46 --> Y=1 & X=9
Regards,
hari
2007-01-16 23:29:45
·
answer #10
·
answered by A.hari 1
·
0⤊
0⤋